Alternativa de energías renovables e investigación aceite de palma biocombustible (2020)
The work focuses on the approach of a master plan and a partial plan that corresponds to the characteristics of the environment, Barrancabermeja-Aguachica, the corridor to be analyzed gives us population data and needs of each region to achieve a development with arguments. With everything discussed in the partial plan is that pollution, and the lack of good infrastructure, is a very strong deficit and we can provide several solutions to the region. Possible solutions are governed by the Action Unit of each of the group members to ensure a concept, analysis, argument and thus achieve the correct execution of the specific projects. The project arises from the need to mitigate the environmental impact generated by the Ecopetrol refinery, in search of a fuel friendly with the biofuel environment), with river transport to the region generating employment opportunities for the inhabitants, providing training, conferences; through the rational care of the resources given to us by the nature of the region.